Faktor-Faktor Yang Mempengaruhi Self Transcendence Perawat: Scoping Review - Imam Abidin; Neti Juniarti; Ahmad Yamin (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2021)
Background: Professional nurses are born from the experience of interacting with other people, in this case, one of which is caring for patients and awareness of themselves/interactions with themselves. According to Pamela G Reed's theory, this interaction and connectedness are related to self-transcendence. Nurses working in emotionally and physically demanding environments develop high levels of intra-connection and high engagement, which facilitate caring interactions with patients and enhance multiple dimensions of their well-being. Self-transcendence tends to accept and like what is done both in daily activities and when interacting with people.Methods: This research is a scoping review. By searching for keyword factors that influence nurses' self-transcendence and nurses' self-transcendence in three data sources, Google Scholar, Crossref and Pubmed using Publish or Perish.Results: There were 5887 articles, and after the selection process, six articles were analyzed. Spirituality is a factor that affects self-transcendence. Besides that, self-transcendence affects self-transcendence in nurses, which affects nurse interactions, work safety climate in the service environment, and fatigue in providing maintenance services.Conclusion: Apart from personal and contextual factors, spiritual factors influence self-transcendence. Self-transcendence can also affect nurse interactions, work safety climate, fatigue, and caring behavior. Keywords: self-transcendence, nurse, nurses' self-transcendence